2008
DOI: 10.1007/s11065-008-9059-9
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Stereotype Threat Literature and Its Application in a Neurological Population

Abstract: Stereotype threat is a situational phenomenon, leading to test performance decrements, in which a member of a stigmatized group feels pressured by the possibility of confirming or being judged by a negative stereotype. This review article highlights the progression of research in the stereotype threat field, and its relevance to neurological populations. Early studies focused on demonstrating this effect in African American, women, and elderly populations. Since this time, research has continued to focus on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 104 publications
1
52
0
3
Order By: Relevance
“…Our findings are well in line with a recent study by Boselie et al (2014), showing that the disruptive effect of pain on task performance in an operationspan task was successfully prevented by experimentally induced optimism, an implicit or unspecific expectation of something positive to happen (Scheier and Carver, 1985). Similar effects of implicit expectations on behavioural performance have been reported in the stereotype-thread literature (Kit et al, 2008). Activating stereotypes, for instance by emphasizing group membership, can influence task performance.…”
Section: Expectancy Modulates Visual Categorization Accuracysupporting
confidence: 91%
“…Our findings are well in line with a recent study by Boselie et al (2014), showing that the disruptive effect of pain on task performance in an operationspan task was successfully prevented by experimentally induced optimism, an implicit or unspecific expectation of something positive to happen (Scheier and Carver, 1985). Similar effects of implicit expectations on behavioural performance have been reported in the stereotype-thread literature (Kit et al, 2008). Activating stereotypes, for instance by emphasizing group membership, can influence task performance.…”
Section: Expectancy Modulates Visual Categorization Accuracysupporting
confidence: 91%
“…If test wiseness varies across groups, individuals in different groups with the same underlying level of the ability measured by the test would have unequal expected scores, which is a definition of differential item functioning (DIF) (Camilli & Shepard, 1994; Thissen, Steinberg, & Wainer, 1993). Other factors representing test bias include reaction to test content (e.g., familiarity, interest) (Brickman et al, 2006; Flaugher, 1978; Stricker & Emmerich, 1999; Teng & Manly, 2005) and cultural factors including stereotype threat, language, or unrepresentative norms (Brickman et al, 2006; Gasquoine, 2009; Kit, Tuokko, & Mateer, 2008; Loewenstein, Arguelles, Arguelles, & Linn-Fuentes, 1994; Manly et al, 2002; Manly, 2008; Teng & Manly, 2005; Whitfield, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…An emerging line of research is investigating ways in which stereotype threat may affect the health outcomes of stigmatized groups (Inzlicht and Kang 2010; Kit et al 2008; Seacat and Mickelson 2009), contribute to racial health disparities (Aronson 2011; Aronson et al 2013; Burgess et al 2010), and influence the training and medical achievement of minorities (Aronson 2011; Burgess et al 2010; Woolf et al 2008). For instance, regarding physical and mental health, Seacat and Mickelson (2009) found that clinically overweight women presented with material designed to activate obesity-related threat reported reduced exercise and dietary intentions relative to their nonthreatened, overweight counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…The few published studies devoted to understanding the health-related parameters of threat are largely narrative (Burgess et al 2010; Kit et al 2008) or qualitative (Woolf et al 2008), or they examine the behaviors of individuals classified with specific health conditions (e.g., schizophrenics; Henry et al 2010) after receiving a threat manipulation. Even threat research that incorporates health-related variables into its methods often assesses academic performance as the dependent variable of interest as opposed to a clear health criterion (Blascovich et al 2001).…”
Section: Introductionmentioning
confidence: 99%